Patients direct costs to undergo TB diagnosis. Issue 1 (December 2016) - de Cuevas, Rachel; Lawson, Lovett; Al-Sonboli, Najla; Al-Aghbari, Nasher; Arbide, Isabel; Sherchand, Jeevan; Nnamdi, Emenyonu; Aseffa, Abraham; Yassin, Mohammed; Abdurrahman, Saddiq; Obasanya, Joshua; Olanrewaju, Oladimeji; et al.
Abstract Background A major impediment to the treatment of TB is a diagnostic process that requires multiple visits. Descriptions of patient costs associated with diagnosis use different protocols and are not comparable. Methods We aimed to describe the direct costs incurred by adults attending TB diagnostic centres in four countries and factors associated with expenditure for diagnosis. Surveys of 2225 adults attending smear-microscopy centres in Nigeria, Nepal, Ethiopia and Yemen. Adults >18 years with cough >2 weeks were enrolled prospectively. Direct costs were quantified using structured questionnaires. Patients with costs >75th quartile were considered to have high expenditure (cases) and compared with patients with costs <75th quartile to identify factors associated with high expenditure. Results The most significant expenses were due to clinic fees and transport. Most participants attended the centres with companions. High expenditure was associated with attending with company, residing in rural areas/other towns and illiteracy. Conclusions The costs incurred by patients are substantial and share common patterns across countries. Removing user fees, transparent charging policies and reimbursing clinic expenses would reduce the poverty-inducing effects of direct diagnostic costs. In locations with limited resources, support could be prioritised for those most at risk of high expenditure; those who are illiterate, attend the service with company and rural residents.